1988
DOI: 10.1161/01.hyp.11.6.509
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive action of parathyroid hormone in hypoparathyroid and hyperparathyroid rats.

Abstract: SUMMARY Experimental and clinical data suggest an association between chronic hyperparathyroidism and hypertension, but acute infusion of parathyroid hormone causes vasodilation and hypotension. These observations imply that chronic and acute parathyroid states affect blood pressure through different mechanism(s), either by modification of vascular receptors or by an ionophoretic effect of parathyroid hormone. The effect of parathyroid status induced by dietary calcium manipulations or by surgical ablation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Nevertheless, reductions in dietary calcium comparable to those used to modify central nervous system calcium levels are reported to alter central nervous system norepinephrine levels. Baksi 122 reported that 8 weeks of a 0.005% calcium diet reduced hypothalamic norepinephrine and dopamine content in Sprague-Dawley rats. Restricted dietary calcium has also been reported to alter peripheral catecholamine levels.…”
mentioning
confidence: 99%
“…Nevertheless, reductions in dietary calcium comparable to those used to modify central nervous system calcium levels are reported to alter central nervous system norepinephrine levels. Baksi 122 reported that 8 weeks of a 0.005% calcium diet reduced hypothalamic norepinephrine and dopamine content in Sprague-Dawley rats. Restricted dietary calcium has also been reported to alter peripheral catecholamine levels.…”
mentioning
confidence: 99%
“…Increased levels of parathyroid hormone are known to activate protein kinase C in cardiac myocytes, leading to hypertrophic growth of the myocardium and exerting an inotropic influence (27,28). In animal models of hypoparathyroidism, infusion of parathyroid hormone causes a hypotensive response by a largely unknown mechanism (29). This patient's calcitonin level was inexplicably elevated and not felt to be the cause of his hypocalcemia.…”
Section: Discussionmentioning
confidence: 85%
“…Schleiffer et al (18) demonstrated that parathyroidectomy of the SHR restricted the blood pressure elevation. Baski (2) reported that while acute PTH infusion in normal rats caused hypotention, chronic PTH infusion caused hypertension contrariwise. This result suggests that the PTH alone is one of the factors that induce the increase in the cell free calcium ion.…”
Section: Discussionmentioning
confidence: 99%